The Dialogical Quality of the Russian Poetry of the Silver Age: A Case Study of Poems about Don Juan - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2021)
The article brings a discussion of three poems of Russian modernist poets that undertake the theme of Don Juan – written by Konstantin Balmont, Valery Bryusov and Nikolai Gumilyov. The purpose is to elucidate the characteristics of the artistic dialogue in the discourse of modernist poetry. Two types of dialogue are discussed: macro- and microdialogue. The former is realised through intertextual forms, the latter – by means of intersubjective forms. When poets refer to the image of Don Juan, one variety of dialogue may well transform into the other. The author of the paper indicates emphatically that the poems under discussion constitute a chain of transformations of the image of Don Juan: the image as proposed by Balmont is then developed by Bryusov and revaluated by Gumilyov. The semantic core of all the three texts is the image of Don Juan as a wanderer who yields to temptations of transient delights.